Rebuking the concept of ageing as a disease. - Mc Crory, Cathal; Kenny, Rose (My University, 2018)
It was with concern that we read the title of a recent Editorial1 in The Lancet Diabetes & Endocrinology entitled "Opening the door to treating ageing as a disease". Although the purpose of the Editorial may have been to stimulate debate, we believe that any attempt to rebrand ageing as a disease is fundamentally misguided and retrograde.
PUBLISHED
Keywords: Ageing